Not without their struggles! Working and living conditions of migrant live-in care workers and a lot to learn for feminist theory - Maier, Carina (Momentum Quarterly, 2022)
The article focuses on transnational gendered (care) labor relations. It takes an analytical perspective from migrant live-in care workers’ political struggles. Starting from the legalization of this sector in Austria and ist specific regulations, the text analyzes the working and living conditions of migrant live-in care workers from an intersectional (queer) feminist economic and ideological critique. A feminist understanding of crisis enables a focus on specific ways of how precarious working conditions, and the permanent crisis of care more generally are made visible and invisible. It shows that in the live-in model, the ideal of care as familial is stabilized. Within the complex relationship between transnational care work and (national) state institutions, the article tries to understand the complexity of migrant live-in care workers’ living and working conditions in the context of transnational social inequality. Following from this, the feminist critique of a system-inherent invisibilization, devaluation, and distribution of care work is linked to elements of care that emphasize the embodied dependencies and relationships and thereby direct attention to an often hidden solidarity between those who care and those who are cared for.